Mode III stress intensity factors of sickle-shaped surface cracks in round bars / Al Emran Ismail - Ismail, Al Emran (Faculty of Mechanical Engineering Universiti Teknologi MARA (UiTM), 2016)
The solutions of stress intensity factors (SIFs) of sickle-shaped surface crack in round bars are not currently available especially when the cracks are subjected to mode III loading. Mode I SIFs can be obtained in open literature however they are also insufficiently completed. Therefore, this paper develops numerically the sickle-shaped crack in round bars using AN SYS finite element program. In order to validate the model, the existing mode I SIFs are used and then compared with the present model. It is found that both models are well agreed with each other. There are two important parameters used such as the crack aspect ratio, a/b and the relative crack depth, a/D ranging between 0.2-1.2 and 0.1-0.6, respectively. SIFs based on J-integral are calculated along the crack fronts for various crack geometries. It is found that the SIFs are significantly affected by a/b and a/D. For the relatively straight-fronted crack (a/b £ 0.2), the SIFs are almost flattened along the crack front. When a/b increased (a/b > 0.2), the SIFs have decreased whereas they are increased when a/D increased. It is also found that the SIFs closed to the outer edge are higher than the SIFs at the deepest crack along the crack front. However when a/b³ 1.2, the role of SIFs along the crack fronts are inversed where lower SIFs are observed at the outer point compared with the middle point.